Applying The Roy Adaptation Model: An Empowerment Approach to Build Psychosocial Resilience in Hypertensive Pregnant Women - Liliek Pratiwi; Siti Harnina Bintari; Dina Nur Anggraini Ningrum; Chatila Maharani (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT Hypertensive Disorders of Pregnancy (HDP) significantly drive Maternal Mortality Rates (MMR) in Garut Regency, exacerbated by poor psychosocial support. This program aimed to empower hypertensive pregnant women by enhancing psychosocial resilience through Roy’s Adaptation Model. Using a Participatory Technology Development approach, 30 pregnant women with gestational hypertension or mild preeclampsia at Tarogong Public Health Center participated in a four-session workshop addressing physiological, self-concept, role function, and interdependence modes. Pre- and post-tests evaluated knowledge, resilience via the Connor-Davidson Resilience Scale (CD-RISC), and blood pressure stability. Participants with 'Good' knowledge surged from 10% to 86.7%. Resilience scores substantially improved in self-concept (+35.7), role function (+27.3), and interdependence (+31.3), shifting coping mechanisms from maladaptive to adaptive. Clinically, average blood pressure decreased by 14.4 mmHg (systolic) and 8.7 mmHg (diastolic), with 83.3% of participants achieving controlled, stable levels. Interventions based on Roy's Adaptation Model effectively strengthen the psychosocial and physiological capacities of hypertensive pregnant women. Integrating a sustainable WhatsApp consultation group with village midwives serves as a vital preventive strategy for early detection and maternal mortality reduction. Keywords: Blood Pressure Stability, Hypertensive Disorders of Pregnancy, Psychosocial Resilience, Roy's Adaptation Model.